COMPASSION-BASED CHARACTER EDUCATION FOR ENHANCING DANCE CREATIVITY AMONG SENIOR HIGH SCHOOL STUDENTS - Ayu Kerti Utami BW; Nyoman Dantes; Desak Putu Parmiti (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
Dance learning in secondary schools often emphasizes technical performance rather than creating supportive learning environments that foster students' creativity and character development. Consequently, students have limited opportunities to express ideas, explore movements creatively, and develop empathy through collaborative learning. Responding to this issue, this study aimed to investigate the implementation of Compassion-Based Character Education and its contribution to enhancing dance creativity among senior high school students at SMA Negeri 2 Negara. This study employed a qualitative approach using an intrinsic case study design. Data were collected through participant observation, in-depth interviews, and document analysis involving teachers, students, and school administrators. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings revealed that Compassion-Based Character Education was successfully integrated into classroom interaction, collaborative learning, and movement exploration through empathy, supportive communication, collaboration, and mutual respect. This implementation contributed positively to students' creativity, particularly in terms of fluency, flexibility, originality, and elaboration of dance movements. The study also identified several supporting and inhibiting factors affecting the implementation process. These findings suggest that Compassion-Based Character Education provides a humanistic pedagogical framework for simultaneously strengthening character education, emotional support, and creativity development in secondary school dance learning.